For he is Muhammad S.A.W., the Rasulullah / Ruzlinda Mustafa - Mustafa, Ruzlinda (Academy of Language Studies, 2022)
12 Rabiulawal, On that special day, The sky was bright, The news was spread, Here comes the rahmat from Allah, Here comes the light for the entire world ,Someone special has been born!, He who will be spreading the words from Allah ,Come what may, nothing can stop his dakwah, For he is protected, guided, and blessed by the Rabb ,For he is Muhammad S.A. W, the Rasulullah